2020
DOI: 10.15252/embj.2019104154
|View full text |Cite
|
Sign up to set email alerts
|

The heat's on: nuclear stress bodies signal intron retention

Abstract: The cellular response to heat shock requires massive adaptation of gene expression driven by the transcription factor HSF1, which assembles in nuclear stress bodies together with human satellite III RNA and numerous splicing factors. In this issue of The EMBO Journal, Ninomiya et al demonstrate that nuclear stress bodies serve as a platform for phosphorylation of the SR protein SRSF9 by the CLK1 kinase, which promotes retention of a large number of introns during the recovery phase from heat shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A common observation in diverse organisms has been the formation of stress granules triggered by adverse environmental conditions, whose composition is variable depending on the organism and on the stress condition [ 9 ]. The participation of stress TFs in the formation of some of these stress bodies has been reported, as is the case of human Hsf1 TF, which initiates the generation of nuclear stress bodies by interaction with pericentric tandem repeats leading to an increased transcription of large heterochromatic regions in response to stress [ 99 , 100 ]. The potential of stress IDTFs and other signaling IDPs to undergo LLPS, and their physicochemical characteristics allowing them to establish diverse protein and nucleic acid interactions, point them as components of stress bodies or condensates, even though its role in the control of transcription is still an open question.…”
Section: Resultsmentioning
confidence: 99%
“…A common observation in diverse organisms has been the formation of stress granules triggered by adverse environmental conditions, whose composition is variable depending on the organism and on the stress condition [ 9 ]. The participation of stress TFs in the formation of some of these stress bodies has been reported, as is the case of human Hsf1 TF, which initiates the generation of nuclear stress bodies by interaction with pericentric tandem repeats leading to an increased transcription of large heterochromatic regions in response to stress [ 99 , 100 ]. The potential of stress IDTFs and other signaling IDPs to undergo LLPS, and their physicochemical characteristics allowing them to establish diverse protein and nucleic acid interactions, point them as components of stress bodies or condensates, even though its role in the control of transcription is still an open question.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we previously found that heat stress alone caused cell death in an iPSC‐derived model of MNs. 16 Furthermore, heat stress, 49 , 50 ageing and neurodegeneration 51 , 52 , 53 all associate with intron retention. 2 , 4 , 54 , 55 Future research will investigate the molecular mechanisms by which elevated temperatures lead to similar responses as those observed in patient‐specific ALS MN cultures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the formation of SGs was proposed to be nucleated by specific protein-mRNA interaction that forms oligomers which are crosslinked by PABP-1 into microscopically visible SGs ( Anderson and Kedersha, 2008 ). Similarly, a number of nuclear bodies, including nucleolus, histone locus bodies (HLBs), Cajal body, Nuclear splicing speckles, paraspeckle, and nuclear stress bodies (nSB) were nucleated by specific RNAs which recruit additional proteins to form microscopically visible granules ( Mao et al, 2011 ; Shevtsov and Dundr, 2011 ; Falahati et al, 2016 ; Falahati and Wieschaus, 2017 ; Erhardt and Stoecklin, 2020 ). However, most of these condensates contain hundreds of proteins that their recruitment and interactions remain uncharacterized.…”
Section: The Biogenesis Of Membrane-less Condensatesmentioning
confidence: 99%